Fibroblast Growth Factor-1 Activates Neurons in the Arcuate Nucleus and Dorsal Vagal Complex - Roberts, Brandon L.; Kim, Eric J.; Lindsley, Sarah R.; Tennant, Katherine G.; Kievit, Paul (Frontiers in Endocrinology, 2021)
Central administration of fibroblast growth factor-1 (FGF1) results in long-lasting resolution of hyperglycemia in various rodent models, but the pre- and postsynaptic mechanisms mediating the central effects of FGF1 are unknown. Here we utilize electrophysiology recordings from neuronal populations in the arcuate nucleus of the hypothalamus (ARH), nucleus of the solitary tract (NTS), and area postrema (AP) to investigate the mechanisms underlying FGF1 actions. While FGF1 did not alter membrane potential in ARH-NPY-GFP neurons, it reversibly depolarized 83% of ARH-POMC-EGFP neurons and decreased the frequency of inhibitory inputs onto ARH-POMC-EGFP neurons. This depolarizing effect persisted in the presence of FGF receptor (R) blocker FIIN1, but was blocked by pretreatment with the voltage-gated sodium channel (VGSC) blocker tetrodotoxin (TTX). Non-FGF1 subfamilies can activate vascular endothelial growth factor receptors (VEGFR). Surprisingly, the VEGFR inhibitors axitinib and BMS605541 blocked FGF1 effects on ARH-POMC-EGFP neurons. We also demonstrate that FGF1 induces c-Fos in the dorsal vagal complex, activates NTS-NPY-GFP neurons through a FGFR mediated pathway, and requires VGSCs to activate AP neurons. We conclude that FGF1 acts in multiple brain regions independent of FGFRs. These studies present anatomical and mechanistic pathways for the future investigation of the pharmacological and physiological role of FGF1 in metabolic processes.